Search analytics: how and what users are looking for - Serrano-Cobos, Jorge (Anuario ThinkEPI, 2011)
Some examples of search terms and phrases used by Google users, which are available free of charge on the Google Adwords service, are discussed. The analysis of why and how the public searches for information can offer interesting guidelines for deciding particular subject headings in libraries, and for search engine optimization (SEO) to improve the position of a website in the search engine results pages.